Ex vivo adenovirus mediated gene transfection of human conjunctival epithelium. Issue 7 (1st July 2001) - Shen, Jikui; Taylor, Neil; Duncan, Linda; Kovesdi, Imre; Bruder, Joseph T; Forrester, John V; Dick, Andrew D
Abstract : AIM: To investigate the efficacy of "ex vivo" adenoviral vector mediated gene transfection of human conjunctival epithelial cell as a possible route for gene therapy for the distribution of anti-inflammatory agents for the potential treatment of immune mediated ocular inflammatory disorders. METHODS: Human conjunctival cells (HCs) were cultured with various concentrations of recombinant adenoviral vectors carrying a reporter gene LacZ, GFP, or an immunomodulating cytokine vIL-10. vIL-10 in culture supernatant was detected by sandwich ELISA and biological activity was assessed by suppression of ConA stimulated splenocyte proliferation. X-gal and GFP expression was assessed by histochemistry. RESULTS: The extent of adenoviral vector mediated transfer of both reporter genes and vIL-10 was dose dependent. LacZ expression could be detected for at least 50 day after infection with multiple of infection (MOI) 200. Following AdCMVvIL-10 transduction, vIL-10 protein expression occurred between 4–6 days post-transduction, and was maintained at a detectable level for at least 1 month. Secreted vIL-10 showed biological activity, significantly inhibiting Con A induced splenocyte proliferation. Additionally, transfection of HCs with two Adv vectors, one carrying LacZ and the other carrying GFP, resulted in co-expression within a single cell. CONCLUSION: These results confirm previous successful adenoviral vector mediated gene transfer to HCs and further show that expression can be maintained. Furthermore the data show HCs can secrete biologically active vIL-10 that could be developed as a strategy to suppress immune mediated disorders. The successful co-transduction of HCs as described for other tissues, opens avenues to develop a multiple target gene therapy locally.